Antibacterial, cytotoxicity and physical properties of laser--silver doped hydroxyapatite layers - Jelinek, M; Kocourek, T; Remsa, J; Weiserová, M; Jurek, K; Mikšovský, J; Strnad, J; Galandáková, Adéla; Ulrichová, J (Materials science & engineering. C, Materials for biological applications, 2013)
Hydroxyapatite layers with silver doping from 0.06 at.% to 14 at.% were prepared by laser deposition. The films' physical properties such as morphology, composition, crystallinity, Young's modulus and microhardness were measured. Films were amorphous or polycrystalline in dependence on deposition temperature (from RT to 600 °C). Antibacterial properties were tested using Escherichia coli and Bacillus subtilis cells. The antibacterial efficacy changed with silver doping from 4% to 100%. Cytotoxicity was studied by a direct contact test. Depending on doping and crystallinity the films were either non-toxic or mildly toxic.
Keywords: Fibroblasts; Microbial Sensitivity Tests; Staphylococcus aureus; Durapatite; krystalizace; tvrdost; Hardness; Crystallization; buněčná smrt; mikrobiální testy citlivosti; modul pružnosti; Microscopy, Electron, Scanning; Escherichia coli; antibakteriální látky; lasery; zvířata; myši; titan; buňky NIH 3T3; Mice; Elastic Modulus; NIH 3T3 Cells; Titanium; Anti-Bacterial Agents; mikroskopie elektronová rastrovací; difrakce rentgenového záření; X-Ray Diffraction; hydroxyapatit; fibroblasty; Animals; Silicon; Cell Death; Lasers; křemík